Nanonization of ethanolic tulsi leaf extract and its major compound eugenol and evaluation of their inhibitory potential against calcium oxalate crystal (a kidney stone component) - Sourav Ghosh; Tarakdas Basu (Nano Express)
The aim of this study was a) to synthesize nanoforms of the whole leaf extract of the flowering herb ‘Tulsi— Ocimum sanctum ’ (regarded as the ‘queen of herbs’ having diverse healing and health-improving properties) and its major constituent eugenol, b) to characterize some of their physico-chemical properties and c) to explore their inhibitory role on formation and disintegration of the kidney stone-former calcium oxalate crystals, through in vitro investigation. Colloidal suspensions of Tulsi-leaf-extract nanoparticles (TLE-NPs) and eugenol nanoparticles (ENPs) were synthesized separately by ultrasonication method through emulsification of hydrophobic TLE/eugenol into hydrophilic protein gelatin. Due to nanonization, water-insoluble TLE/eugenol became water-soluble and thus bioavailable. The average size of the particles was about 35nm for TLE-NPs and 25 nm for ENPs, entrapment efficiency of TLE and eugenol within gelatin was about 20 and 80% respectively, and the release rate of TLE/eugenol from gelatin cap was slow and sustained throughout 72 h for TLE-NPs and 120 h for ENPs. When spectroscopic and microscopic studies were performed on the formation and disintegration of calcium oxalate crystals in presence of TLE-NP and ENP, both types of particles depicted significant inhibitory potential on crystal formation and disintegrating potential on pre-formed crystals, compared to the same doses of their bulk forms i.e., bare TLE and eugenol; ENP was more potent than TLE-NP with respect to crystallization inhibitory activity, whereas they were comparable in crystal disintegration potency. Future in vivo pharmacological and toxicological studies will surely lead to the development of the TLE-NPs and ENPs as potential therapeutic agents against calcium oxalate pathogenesis.